Strategi Komunikasi Politik Amerika Serikat dalam Memanfaatkan Hollywood sebagai Media untuk Memperkuat Dominasi Global - M. Elfan Kaukab; Atinia Hidayah (Department of Political Science - Universitas Sains Al-Qur’an, 2020)
The United States has a range of methods that is strong enough to carry out propaganda. The role of the mass media and Hollywood movie industry have become a tool of war used by the United States. The media is very influential in persuading one's thoughts and actions. Media is also able to carry out its social construction to wrap reality into an ideal one which is strongly believed because it has been occurring over periods of time. The purpose of this research is to analyze the United States in dominating global influence through Hollywood as a media that plays a role in running propaganda politics. The method used is an explanative analysis of the Black Panther movie. The result of this research is the significant role of the mass media in reconstructing global social conditions by the United States which tries to maintain its dominance through various kinds of propaganda, including those carried out through the production of Hollywood movies.